Needs Analysis and Design of Martapura Kingdom Numerical Teaching Materials based on Android with the help of I-Spring suite for Elementary School students in Samarinda City. - Saputra, Yulian Widya; Kurniawan, Kurniawan; Hidayah, Fitria Nurul; Mujahadah, Mujahadah (Faculty of Teacher Training and Education, Mulawarman University, 2023)
The advantage of the mobile learning concept is that learning can be accessed at any time because it is installed on a smartphone and can be applied to mathematics courses in ethno-mathematics-themed elementary schools. elementary school students in Samarinda City. This research is part of Research and Development (R&D) to develop teaching materials using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. These five stages the researcher uses the Analysis and Design stage. Data collection used a questionnaire filled out by elementary school students and interviews with teachers. The data analysis technique used in this study is a qualitative descriptive data analysis technique and a quantitative descriptive data analysis technique. The research results obtained the results of the stages of needs analysis, from stakeholders and development design. Based on the needs analysis conducted, it was found that 51.6% did not know the oldest kingdom in the archipelago, 19% of learning media still used PowerPoint, 19% visual aids, 20% videos. Regarding gadget or cellphone ownership, 100% of students have their own cellphone and still use it to play online games. The results of the subsequent questionnaire 100% did not know the figure of Raja Mulawarman, 57.1% of students stated that they had never been taught mathematics related to cultural history (ethnomatematics). Teacher interviews in the mathematics learning process tend to use power point and have never used android media. The teacher has never delivered ethnomathematics-based mathematics material. The results of the design stage, the researcher designed math teaching materials (island numbers) based on android applications.